2003
DOI: 10.1080/15438600490277860
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Linking in Collagen by Nonenzymatic Glycation Increases the Matrix Stiffness in Rabbit Achilles Tendon

Abstract: Nonenzymatic glycation of connective tissue matrix proteins is a major contributor to the pathology of diabetes and aging. Previously the author and colleagues have shown that nonenzymatic glycation significantly enhances the matrix stability in the Achilles tendon (Reddy et al., 2002, Arch. Biochem. Biophys., 399, 174-180). The present study was designed to gain further insight into glycation-induced collagen cross-linking and its relationship to matrix stiffness in the rabbit Achilles tendon. The glycation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
148
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(163 citation statements)
references
References 35 publications
12
148
0
1
Order By: Relevance
“…First, the formation of AGEs and crosslinks induced by ribose treatment was not directly quantified, however previous investigations have provided direct molecular evidence for pentosidine formation in tissue incubated with ribose [47,48]. Additionally, in this work the indirect measurements of AGE formation by fluorescence showed clear changes after ribose treatment, comparable to the previous reports [47][48][49].…”
Section: Discussionsupporting
confidence: 80%
“…First, the formation of AGEs and crosslinks induced by ribose treatment was not directly quantified, however previous investigations have provided direct molecular evidence for pentosidine formation in tissue incubated with ribose [47,48]. Additionally, in this work the indirect measurements of AGE formation by fluorescence showed clear changes after ribose treatment, comparable to the previous reports [47][48][49].…”
Section: Discussionsupporting
confidence: 80%
“…Non-enzymatic glycation was probably the responsible for the increase of this value due to the covalent bonds of advanced glycation agents between collagenous structures 8,9 . Such results corroborate those found in other studies that showed an increase in the elastic modulus of the calcaneal tendon of rabbits undergoing non-enzymatic glycation 28 and Wistar rats induced to diabetes mellitus 29 . The decrease of elastic modulus to normal levels in diabetic animals subjected to resistance training demonstrated the restoration of the viscoelastic capability of the tendon, resulting from jump training in an aquatic environment.…”
Section: Discussionsupporting
confidence: 82%
“…However, the TSA of this group was the smallest found, which was the main reason for the increase of this parameter. In tendons subjected to non-enzymatic glycation some authors have also found greater values of maximum tensile strength 28 . Our training protocol was able to reduce the tension and normalize its value when compared to the SCG.…”
Section: Discussionmentioning
confidence: 91%
“…In work [82], an increase in the glucosapane content in the skin with age and with the development of hyperglycemia in patients with type 1 diabetes mellitus was recorded. After eight months of glycation of the rabbit Achilles tendon in ribose solution [139] the increased maximum load, deformation stress, Young modulus of elasticity, and viscosity, indicating the fact that the glycation increases the stiffness of the tendon matrix, were observed. The tendon glycation was found to lead to significant reduction of the soluble collagen content and considerable increase of insoluble collagen and pentosidine content.…”
Section: Glycation and Non-enzymatic Glycation Of Proteinsmentioning
confidence: 99%
“…The glycation is a result of the interaction between the glucose molecules and the proteins, which leads to the change of protein structure and to the restriction of To study the glycation of proteins, both the samples of tissues and cells from the objects with natural or artificially induced diabetes mellitus (in vivo glycation), as well as the samples that has been glycated under in vitro conditions are used. Studies of in vitro glycation refer, for example, to human placental type IV collagen, performed by fluorescence analysis, as well as by electrophoresis and densitometry [134]; collagen of bovine skin -using multiphoton microscopy [34]; hemoglobin -by optical coherent tomography [135][136][137], refractometry and IR spectroscopy [122], as well as biochemical analysis [138]; albumin -using fluorescence spectroscopy [70], refractometry [122], and terahertz spectroscopy [138]; collagen of the tendon -through biochemical and biomechanical analyzes [139], as well as to collagen hydrogels -using multispectral fluorescence life time imaging (FLIM) [140]; by incubation in ribose [37,134,139,140], glucose [70,122,135,138,141] or fructose [70,141] solutions. All of them show a sufficiently effective glycation of proteins during 10-11 days of incubation, a change in the mechanical properties of tissues due to the formation of collagen cross-links.…”
Section: Glycation and Non-enzymatic Glycation Of Proteinsmentioning
confidence: 99%